CT and MRI compatibility of flexible 3D‐printed materials for soft actuators and robots used in image‐guided interventions - Neumann, Wiebke; Pusch, Tim P.; Siegfarth, Marius; Schad, Lothar R.; Stallkamp, Jan (Medical physics, 2019)
Purpose - Three‐dimensional (3D) printing allows for the fabrication of medical devices with complex geometries, such as soft actuators and robots that can be used in image‐guided interventions.
First published: 06 October 2019
Gesehen am 26.01.2021